EVALUASI PEMAHAMAN PENGETAHUAN KUALITAS DAN PEMELIHARAAN LAPANGAN GOLF PADA DEPARTEMEN GOLF OPERASIONAL IMPERIAL KLUB GOLF DI LIPPO VILLAGETANGERANG - Ersia Rahma Dewi (Universitas Mercu Buana, 2014)
Abstract. Research method that used is descriptive analysis. The subject of thisresearch was employees golf operation department at Imperial Klub Golf, PTLippo Karawaci. Tbk, Lippo Village, Tangerang. This research was begin bypreparing the test in the form of multiple reasoned choice (two-tier diagnostictest), those questions were selected based on the indicators which had to beachieved by the employees in accordance to the standard and basic competence asof employees golf operation. The results of the evaluation showing the employeesunderstanding not met with company targets. Based of result of the research, it issuggested that management can develop learning strategies and models toimprove the understanding of employees with a combination of conventional andactive learning strategies. Recommended of learning strategies and models withadapted to current conditions are: (1) Strategy Expository (direct instruction),through lectures learning methods (lecture) and demonstrations. (2) Affectivelearning strategies, through the provision of task learning methods (modularizedinstruction) and exercise (drill and practice). (3) Group of cooperative learningstrategies (cooperative learning), the learning method of discussion and frequentlyasked questions. (4) The learning strategies of Conceptual Teaching and Learning(CTL), the learning method demonstration, sociodrama, field trips (fieldexperience)Keyword: Knowledge Quality and Maintenance Understanding, Two-TierDiagnostic Test, Learning Strategies and Models.